HbSC Disease and Spontaneous Epidural Hematoma with Kernohan’s Notch Phenomena - Meera Yogarajah; Chidozie Charles Agu; Bhradeev Sivasambu; Mark A. Mittler (Case Reports in Hematology)
Spontaneous (nontraumatic) acute epidural hematoma is a rare and poorly understood complication of sickle cell disease. A 19-year-old African American male with hemoglobin SC disease (HbSC) presented with generalized body aches and was managed for acute painful crisis. During his hospital stay he developed rapid deterioration of his mental status and computed topography revealed a spontaneous massive epidural hematoma with mass effect and midline shift with Kernohan’s notch phenomena for which urgent craniotomy and evacuation was done. We report the first case of HbSC disease associated with catastrophic epidural hematoma progressing to transtentorial herniation and Kernohan’s notch phenomena within few hours with rapid clinical deterioration. The etiopathogenesis and the rare presentation are discussed in detail in this case report.